Pengaruh Semangat Kerja, Disiplin Kerja, dan Beban Kerja Terhadap Produktivitas Kerja Karyawan PT. Trigon Scientific Indonesia. - Dava Aji Pratama; Sonny Subroto Maheri Laksono; Nuril Aulia Munawaroh (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
This research aims to explore how Work Spirit, Work Discipline, and Workload affect employee work productivity at PT. Trigon Scientific Indonesia. This study employs a quantitative research approach with an associative method. The population for this study includes all employees of PT. Trigon Scientific Indonesia, with a sample size of 50 respondents. For testing, the researcher used tests for Validity and Reliability, as well as Classical Assumption Tests, which consist of Normality Test, Linearity Test, Heteroskedasticity Test, and Multicollinearity Test. The analysis technique used is Multiple Linear Regression Analysis, t-Test, F-Test, and Coefficient of Determination (R2). The results of the research indicate that in the Work Spirit variable, there is a positive and significant influence on Work Productivity. In the Work Discipline variable, there is a negative and insignificant influence on Work Productivity. And in the Workload variable, there is a negative and insignificant influence on Work Productivity. The result of the F-test is stated as positive and significant.